Dismissed Content and Discontent: An Analysis of the Strategic Aspects of Actor-Network Theory - Neyland, D (Sage, 2006)
Actor-network theory (ANT) has contributed greatly to the development of science and technology studies. However, recent critiques appear to have left ANT in a gloomy theoretical black box. What is the likelihood of ANT exiting its current theoretical discontent? Is ANT worthy of salvation and on what grounds? Law argues that recent critiques stem from ANT’s development into a particular theoretical strategy. However, this article will argue that by focusing on strategy as messy and impure, ANT can be afforded the opportunity to shift from a fixed approach to an ambiguous and contingent strategy, well placed to carry on. The article achieves such an argument by first highlighting how ANT has contributed to a recent study of strategy in action; second, by outlining the strategic aspects of ANT; and third, by using the study of strategy in action as a means of engaging with ANT’s current theoretical discontent.